APSS-ASJ Best Clinical Research Award: Predictability of Curve Progression in Adolescent Idiopathic Scoliosis Using the Distal Radius and Ulna Classification - Jason Pui Yin Cheung; Prudence Wing Hang Cheung; Dino Samartzis; Keith Dip-Kei Luk (Asian Spine Journal, 2018)
Study DesignProspective study.PurposeTo determine the risk of clinically significant curve progression in adolescent idiopathic scoliosis (AIS) based on the initial Cobb angle and to test the utility of the distal radius and ulna (DRU) classification in predicting these outcomes.Overview of LiteratureDetermining the remaining growth potential in AIS patients is necessary for predicting prognosis and initiating treatment. Limiting the maturity Cobb angle to <40° and <50° reduces the risk of adulthood progression and need for surgery, respectively. The risk of curve progression is the greatest with skeletally immature patients and thus warrants close monitoring or early intervention. Many parameters exist for measuring the skeletal maturity status in AIS patients, but the DRU classification has been shown to be superior in predicting peak growth and growth cessation. However, its predictive capabilities for curve progression are unknown.MethodsTotally, 513 AIS patients who presented with Risser 0–3 were followed until either skeletal maturity or the need for surgery, with a minimum 2-year follow-up period. Outcomes of 40° and 50° were used for probability analysis based on the cut-offs of adulthood progression risk and surgical threshold, respectively.ResultsAt the R6/U5 grade, most curves (probability of ≥48.1%–55.5%) beyond a Cobb angle of 25° progressed to the 40° threshold. For curves of ≥35°, there was a high risk of unfavorable outcomes, regardless of skeletal maturity. Most patients with the R9 grade did not progress, regardless of the initial curve magnitude (probability of 0% to reach the 50° threshold for an initial Cobb angle of ≥35°).ConclusionsThis large-scale study illustrates the utility of the DRU classification for predicting curve progression and how it may effectively guide the timing of surgery. Bracing may be indicated for skeletally immature patients at an initial Cobb angle of 25°, and those with a scoliosis ≥35° are at an increased risk of an unfavorable outcome, despite being near skeletal maturity.